2D analysis of intergranular dynamic crack propagation in polycrystalline materials a multiscale cohesive zone model and dual reciprocity boundary elements. (February 2016) - Galvis, A.F.; Sollero, P.
Highlights: We model the atomistic scale in interfaces of polycrystalline materials using BEM. Using dual reciprocity BEM, we model the dynamic displacement field in the mesoscale. We proposed a failure criterion based on the average distance of the atomic cell. Simulations of dynamic intergranular crack propagation show failure in the mesoscale. Abstract: This work analyses the mechanical behaviour and dynamic intergranular fracture of polycrystalline materials, combining the mesoscale to consider the heterogeneities and anisotropy of the elastic material properties and the atomistic scale to include atomic separation effects. The Dual Reciprocity Boundary Element Method is used to evaluate the dynamic displacement field at the mesoscale. the Multiscale Cohesive Zone Model is used to characterize the crack onset and propagation model of atomic interactions using the Lennard–Jones potential and a failure criterion is also introduced in this formulation. Simulations of dynamic intergranular crack propagation are presented to capture material failure at the microscale.